The elephant in the room: a spatial interrogation of the tensions between animals and man-made environments sets within the zoo lake precinct - Collins, Tamaryn-Jade (My University, 2019)
The Zoological Garden typology, a historical point of controversy and tension, has suffered in the contemporary fabric to remain a relevant public space. The public image of the zoo has been tarnished by the cruelty of the past, tensions of the present and an undetermined future, that have collectively manifested the zoo as the public face of an accumulated societal guilt. Despite such scrutiny, the zoo cannot be discarded from the spatial planning of our cities. The typology is a unique example of a green public space that provides a direct urban connection to the animal world. The narrative of the typology has seen many timely updates from the early aristocratic menageries to the cutting edge Unzoo theory making waves in current zoological conversations. How will built form within the Johannesburg Zoo adapt when enclosures disappear and the line between animal and human space becomes blurred? In understanding this adaption, one will need a comprehension of the current societal context. The 21st century Johannesburg society is in a dilemma with regards to the zoo typology. They criticize the memory of the archetype that no longer aligns with how it functions to date, which is surprising in a society that has information at the (literal) tips of their fingers. The zoo finds itself chastised for its entrapment of wildlife but sees a large number of children visitors annually. This fiercely critical society has, at the same time, seen an increased popularity in exotic pet keeping. These conundrums built to a public tension surrounding the typology as it sits uncomfortably in the consciousness of society, balancing between a traditional zoological garden and a progressive Unzoo. The proposal investigates connection as a tool in elevating this unease while highlighting these tensions through built form. The design intervention reconnects the once consolidated and Johannesburg Zoo, with a large scaled landscaped bridge. The landscaped linkage will be the spatial expression of a transitional buffer between the public Zoo Lake Park area and the slightly privatized Johannesburg Zoo grounds. If the proposal hopes to present a new form of zoological architectural expression, it will need to address more than a lack of spatial connection. The Johannesburg Zoo and Zoo Lake area are one of the largest green public spaces located within a 3km radius of the city centre. However, the site remains unannounced with no vertical anchor. The zoo specifically, has internalized itself which exacerbates public naivety regarding how the space functions and what the typology wishes to be interpreted. The proposal investigates the power of architectural land marking. The proposed icon for the zoo and Zoo Lake area should be carefully considered and artfully constructed as it represents the first impression of the zoo and Zoo Lake Area. An aviary has been proposed as the visual icon for the landscaped linkage and, by extension, the Johannesburg Zoo and Zoo Lake area. Aviaries are the least lambasted of all enclosures within the zoo, yet they entrap the animal in both the vertical and horizontal plane. The aviary is proposed to be the poignant vehicle of challenging the opinions of the public while embodying the social tensions in built form. The proposed architecture aims to be as critical as the society it finds itself in, yet the enveloping nature of the aviary allows the user experience to be unique and captivating. A consistent thread that has remained as design objective through the inception of the proposal is the inspiration taken from a childhood experience of the zoo. Capturing that sensory submergence within the space of the proposal will separate the project from merely a space that educates, to a space which illuminates. The future of the functionality of the zoo is undoubtedly based in education.
Keywords: Zoos--South Africa--Johannesburg; City planning--Environmental aspects--South Africa; Urban parks--South Africa|zJohannesburg--Designs and plans